Chair of peace, communication and university: Comparative analysis - Dueñas, Félix; Peña, Diego; García, Luis; Duque, Fanny (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The research seeks to answer the questions: what is the balance of implementation of the Peace Chair in 4 communication programs in Bogota, since its regulation in 2015? and what are the prospects for improvement derived from the analysis of its incorporation into the curricula? To solve such questions, a qualitative research approach is proposed, supported by documentary and case study types and techniques such as content analysis, focus group, and interview, with which it is expected to consolidate information on the implementation of peace in four communication programs in Bogotá.